A disintegrin and metalloprotease 23 hypermethylation predicts decreased disease‐free survival in low‐risk breast cancer patients. Issue 5 (18th March 2019) - Zmetakova, Iveta; Kalinkova, Lenka; Smolkova, Bozena; Horvathova Kajabova, Viera; Cierna, Zuzana; Danihel, Ludovit; Bohac, Martin; Sedlackova, Tatiana; Minarik, Gabriel; Karaba, Marian; Benca, Juraj; Cihova, Marina; et al.
Abstract : A Disintegrin And Metalloprotease 23 (ADAM23), a member of the ADAM family, is involved in neuronal differentiation and cancer. ADAM23 is considered a possible tumor suppressor gene and is frequently downregulated in various types of malignancies. Its epigenetic silencing through promoter hypermethylation was observed in breast cancer (BC). In the present study, we evaluated the prognostic significance of ADAM23 promoter methylation for hematogenous spread and disease‐free survival (DFS). Pyrosequencing was used to quantify ADAM23 methylation in tumors of 203 BC patients. Presence of circulating tumor cells (CTC) in their peripheral blood was detected by quantitative RT‐PCR. Expression of epithelial ( KRT19 ) or mesenchymal (epithelial‐mesenchymal transition [EMT]‐inducing transcription factors TWIST1, SNAI1, SLUG and ZEB1 ) mRNA transcripts was examined in CD45‐depleted peripheral blood mononuclear cells. ADAM23 methylation was significantly lower in tumors of patients with the mesenchymal CTC ( P = .006). It positively correlated with Ki‐67 proliferation, especially in mesenchymal CTC‐negative patients ( P = .001). In low‐risk patients, characterized by low Ki‐67 and mesenchymal CTC absence, ADAM23 hypermethylation was an independent predictor of DFS ( P = .006). Our results indicate that ADAM23 is likely involved in BC progression and dissemination of mesenchymal CTC. ADAM23 methylation has the potential to function as a novel prognostic marker and therapeutic target. Abstract : In this study, we evaluated the prognostic significance of ADAM23 promoter methylation for hematogenous spread and disease‐free survival (DFS). Although ADAM23 methylation was significantly lower in tumors of patients having mesenchymal circulating tumor cells (CTC) in peripheral blood, in patients without mesenchymal CTC, ADAM23 hypermethylation was an independent predictor of DFS. Our results indicate that ADAM23 is likely involved in epithelial‐mesenchymal transition and breast cancer progression.